The Examination of the Decline of Philosophy of Education with Institutional Theory: A Focus on the Last Three Decades - Colgan, Andrew D. (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2018)
Many symposia and special journal issues over the last several decades have been devoted to concerns over the decline of philosophy in teacher education programs. I pursued an answer for my doctoral project and found institutional explanations are rarely invoked in the “decline literature.” I have sketched here the theory, and have shown it to be equally applicable to the last several decades of this literature. I argue that institutional organizational theory (IOT) shows how teacher education institutions have changed over time in a way that ultimately rendered the environment less and less hospitable to philosophy of education curriculum and faculty. Particular attention is paid to the educational context of Ontario, Canada, but I also include the wider American and British decline literature. In the final pages I offer de-institutionalizing solutions that, if realized, could provide a new soil in which philosophy and other humanities fields could take root again in teacher preparation programs.